The significance of calcium ions in cerebral ischemia-reperfusion injury: mechanisms and intervention strategies - Li, Yong-Wang; Liu, Yu; Luo, Sheng-Zhen; Huang, Xiao-Juan; Shen, Yan; Wang, Wei-Si; Lang, Zhi-Chen (Frontiers in Molecular Biosciences, 2025)
Cerebral ischemia-reperfusion injury (CIRI) represents a multifaceted pathological phenomenon characterized by an array of molecular and cellular mechanisms, which significantly contribute to neurological dysfunction. Evidence suggests that calcium ions play an indispensable role in this context, as abnormal elevations in calcium concentrations exacerbate neuronal injury and intensify functional deficits. These ions are integral not only for intracellular signaling pathways but also for various pathological processes, such as programmed cell death, inflammatory responses, and oxidative stress. This review article elucidates the physiological framework of calcium homeostasis and the precise mechanisms through which calcium ions influence CIRI. Moreover, it addresses potential intervention strategies, including calcium channel blockers, calmodulin (CaM) inhibitors, antioxidants, and anti-inflammatory agents. Despite the proposal of certain intervention strategies, their effectiveness and safety in clinical settings warrant further scrutiny. In conclusion, the article highlights the limitations of current research and anticipates future investigative trajectories, aiming to provide a theoretical foundation and reference for the development of more efficacious treatment modalities.